Percepção da criança sobre a hospitalização - Sanches, Débora Paulino [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Regardless of their age, hospitalized children suffer from being separated from their mothers or their attachment figures. Hospitalization is a process that is difficult for children to cope with due to their separation from families, everyday environments and embedded disease scenarios. According to age, the intensity of such suffering is related to the development phase in which a child is found. The health care professionals that are close to children, not only as concerns care provision, but also emotionally, should be knowledgeable about the mother-child attachment. emotionally, should be knowledgeable about the mother-child attachment. To evaluate children’s perception of hospitalization. The study was conducted at the pediatric hospitalization unit of the Botucatu School of Medicine University Hospital – UNESP by means of interviews with hospitalized children aged 7 – 12 years and by using content analysis according to Bardin. Most of the interviewed children did not like the hospital environment and reported to miss their homes. From their statements, they showed their dissatisfaction in relation to pain and their submission to invasive procedures, which were the main complaints during the interviews. Our results agree with those found in the literature in relation to the hospital environment when the children reported the fact that they missed their homes as a difficulty to adapt. The analysis of results in this study and in previous ones led to the reflection on the importance of the presence of a relative during children’s hospitalization and the adaptation process. Despite their dissatisfaction in relation to invasive procedures, none of the children tried to stop the performance of tests and understood their importance. This is a characteristic of the operational phase, which comprises the development of perception of a whole situation and is when... (Complete abstract click electronic access below)

A criança submetida à hospitalização, independente da idade, sofre com a separação da mãe ou figura de apego. A hospitalização é um processo de difícil enfrentamento para a criança, pela separação da família, do ambiente cotidiano e pelo contexto de doença embutido. De acordo com a idade, relaciona-se a intensidade desse sofrimento com a fase de desenvolvimento que a criança se encontra. O profissional de saúde que estará próximo a criança não apenas em relação ao cuidado, mas também emocionalmente, deve ter como parte da sua formação o conhecimento do apego entre mãe e filho. Avaliar a percepção da criança sobre a hospitalização. O estudo foi realizado na unidade de internação pediátrica do HC – UNESP, através de entrevista com crianças internadas de 7 – 12 anos de idade e com análise de conteúdo segundo Bardin. A maior parte das crianças entrevistadas não gostava do ambiente hospitalar, relatando saudade de casa. Elas demonstraram através da fala o descontentamento com a dor e com a submissão a procedimentos invasivos, sendo essas as principais queixas durante a entrevista. Nossos resultados vêm de encontro com achados na literatura em relação ao ambiente hospitalar quando as crianças relataram saudade como dificuldade para adaptação. A análise dos resultados desse trabalho e de trabalhos anteriores a esse, levaram a reflexão sobre a importância da presença do familiar durante a internação da criança e o processo de adaptação. Apesar do descontentamento em relação aos procedimentos invasivos, nenhuma das crianças tentou impedir a realização do exame, entendendo a sua importância. Essa é uma característica fase operacional a qual fazem parte, o desenvolvimento da percepção do todo, deixando o egocentrismo da fase anterior e conferindo melhor aceitação. Conclui-se a partir dessa análise que as crianças ainda têm... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Criança – Assistência hospitalar; Enfermagem pediatrica